Pengaruh Disiplin Kerja dan Komunikasi Terhadap Kinerja Pegawai di Dinas Pemberdayaan Masyarakat Desa (PMD) Kabupaten Musi Rawas Utara - Yulfa Rabeta; Rudi Azhar; Yuli Efriyanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The purpose of this study was to determine the effect of work discipline and communication on employee performance at the Village Community Empowerment Service (PMD) of North Musi Rawas Regency. The population and research sample amounted to 34 people. Methods of data analysis using quantitative analysis. The results showed that work discipline had an effect on employee performance. While the t-test explained that the discipline variable (X1) on performance showed the value of tcount = 7.517, which was greater than the ttable value of 1.692 with a significant level = 0.000 < (a) 0.05, this indicates Ha is accepted. and partially discipline variable has a significant influence on performance. Communication on Employee Performance The results of the t-test of the communication variable (X2) on performance show the value of tcount = 7.756 Greater than the value of ttable 1.692 with a significant level = 0.000 < (a) 0.05, this shows Ha is accepted and partially the communication variable has an influence significant to performance. Based on the recapitulation of multiple linear regression test results, it was found that the Fcount value obtained was 52.720 > Ftable = 3.28 and the simultaneous significance level of sig F was 0.000. This shows that together (simultaneously) the independent variables of research (discipline and communication) have a significant effect on the dependent variable (performance).